2019
DOI: 10.1177/0022034519831931
|View full text |Cite
|
Sign up to set email alerts
|

MMP-8-Responsive Polyethylene Glycol Hydrogel for Intraoral Drug Delivery

Abstract: Currently available drug delivery systems for oral diseases suffer from short retention time and poor local concentrations at the target site. A biodegradable stimulus-responsive hydrogel was synthesized in the present study to evaluate its application as an environmentally sensitive carrier for on-demand intraoral drug delivery. The hydrogel was synthesized from diacrylate-containing polyethylene glycol–based scaffolds and a cysteine-terminated peptide crosslinker (CGPQG↓IWGQC) via a Michael-type addition rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 29 publications
0
42
0
Order By: Relevance
“…An MMP 8-responsive, polymeric hydrogel was developed from a diacrylate-containing polyethylene glycol-based moiety, along with a cysteine-terminated peptide cross-linker (CGPQG↓IWGQC). The hydrogels were encapsulated with BSA, minocycline hydrochloride, and antibacterial peptide KSL to target chronic periodontitis and peri-implantitis [ 158 ].…”
Section: Stimuli-responsive Polymeric Nanocarriers For Drug and Gmentioning
confidence: 99%
“…An MMP 8-responsive, polymeric hydrogel was developed from a diacrylate-containing polyethylene glycol-based moiety, along with a cysteine-terminated peptide cross-linker (CGPQG↓IWGQC). The hydrogels were encapsulated with BSA, minocycline hydrochloride, and antibacterial peptide KSL to target chronic periodontitis and peri-implantitis [ 158 ].…”
Section: Stimuli-responsive Polymeric Nanocarriers For Drug and Gmentioning
confidence: 99%
“…Therefore, MMPs could act as stimuli for novel DDS. Guo et al designed an MMP-8-responsive hydrogel and demonstrated that it was a promising candidate for on-demand intraoral localized drug delivery [48].…”
Section: The Stimuli-responsive Dds For Oral Infectious Diseasesmentioning
confidence: 99%
“…The DDS could react to specific conditions of oral cavity such as pH, temperature, enzymes, and provide more accurate drug delivery. These intelligent materials provide more possibilities for oral biomaterials research and the treatment for oral diseases [47][48][49].In this review, we will focus on the recent work and emerging applications of DDS in the prevention and treatment of common oral infectious diseases, including dental caries, periodontitis, peri-implantitis, and oral candidiasis, in order to find out the current challenges and opportunities for future research.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Among drugs profile, doxycycline, tetracycline, metronidazole, and minocycline have been selected as antibiotics to be incorporated in the delivery system . Besides antibiotics, antimicrobial peptides have been investigated as drug possibilities to fight oral infections . Further, depending on the target, biomaterial modifications can be employed on different parts of implants to either prevent infection or treat peri‐implantitis.…”
Section: Biomaterial‐based Solutions As Future Perspectives To Prevenmentioning
confidence: 99%